npj 2D Materials and Applications - Kis, Andras; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj 2D Materials and Applications considers research that explores the fundamental behavior, synthesis, properties and applications of existing and emerging 2D materials. The journal covers a broad range of topics including but not limited to: 2D materials in all their forms Fundamental understanding of the basic science of 2D materials Chemical and functionalization strategies for 2D materials 2D material heterostructures and devices Properties of 2D materials Electronic, magnetic, spintronic, photonic, and mechanical properties of 2D materials Synthesis and characterization of 2D materials Applications of 2D materials in various domains, including energy storage and conversion, thermal management, electronics, quantum science and technology Environmental impact of 2D materials The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by 2D materials experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Materials science; Nanotechnology; Surfaces (Technology).; Thin films; Materials Science; Nanotechnology; Surfaces, Interfaces and Thin Film